KEMAMPUAN KOGNITIF ANAK DALAM PEMECAHAN MASALAH MELALUI MEDIA MONOPOLI - Marhamah Jalilah; Syah Khalif Alam (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2018)
Cognitive abilities are thinking skills that have the knowledge, intelligence and relationships of students with their environment. Effective learning for early childhood education, needs to be supported by a conducive learning environment and atmosphere, through play activities. To accustom children to think critically and creatively in solving a problem, researchers used a monopoly game media to develop cognitive abilities in problem solving in children aged 5-6 years in group B of Elektrika Kindergarten. The study was conducted by quasi-pretest and posttest experimental methods in the experimental and control groups. The results showed that the experimental class was 34,167% while the control was 20,875%. This increase was also seen from the results of the percentage value in the N-gain test with a value of 29.142% in the experiments and controls of 20.571%. This shows that the problem solving ability of groups whose learning uses media monopoly is better than groups that use ordinary learning.